Boosting Nepalese Global Trade Performance through Trust and Reputation in Correspondent Banking - Adhikari, Hem Kumari; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
Nepal is an import-based country where International trade and foreign payments remain critical economic challenge. In the context of increasing global fraud and de-risking practices, trustworthiness has become a key concern for banking industries. This study examines how the trust and reputation of correspondent banks shape the international trade-finance performance of Nepalese commercial banks. Using Deductive approach and cross sectional non experimental research design, 300 professionals from Nepalese all commercial banks with distinct departments like as: Remittance/ SWIFT, Compliance /AML, Trade Finance and Top Management. A structured questionnaire under three subheadings i.e. reliability, compliance creditability and stability of relationship which are the dimensions of Trust and Reputation of a correspondent banking were used to gain the aptitudes of professionals. Descriptive Analysis results show the consistency of trust and reputations sub themes i.e. realibility, compliance credibility and stability of relationship. Chi-square tests’ results establish the significant association between overall trust/reputation and trade finance facilitation performance measured as χ² = 2115.276, p <0.05. The study’s findings suggest that Correspondent Banks improve coordination and monitoring the process which accelerates cross-border payments, strengths the letter of LC. High regulatory regulations and global tendency of banks avoiding risk remains significant challenge. This paper recommends for accountable AML/CFT capabilities, wide correspondent portfolios and the strategic use of global assurance to maintain a path access and transform reputation and trustworthiness in to measurable trade- service benefits.